Diagnóstico de la situación de salud animal en la zona fronteriza de la Amazonía Colombiana. - Urbina Amaris, Mairo E.; Cárdenas Zorro, Jaime; Roa, Bonilla, L. (Instituto Colombiano Agropecuario, 1978)
Salud animal